ANALISIS FAKTOR RISIKO PERDARAHAN PASCAPERSALINAN PRIMER PADA PERSALINAN SPONTAN DAN SEKSIO SESAR ATAS INDIKASI KEDARURATAN DI RSIABUDI KEMULIAAN PERIODE JANUARI 2010- DESEMBER 2014 - Aini Fuada Sardjono (2015)
Maternal death in the world was mostly caused by hemorrhage. Primary postpartum hemorrhage was bleeding that occured when the birth completed during the first 24 hours. Risk factor of Primary postpartum hemorrhage consisted of antepartum, intrapartum and postpartum. The main purpose of this research was to investigate the risk factor in antepartum, which was consists of age, parity and amount of hemoglobin and the type of delivery method (spontaneous birth and emergency caesarean section). The research was carried out using analytic method focused in case control. There were 164 mother whom utilizing medical records. The result of univariate showed in this research were the most type of delivery in primary postpartum hemorrhage was spontaneous birth (78%), the most age was 20-35 years old (64%). The most parity in primary postpartum hemorrhage was primpara and grandemultipara (70,7%) for the most amount of hemoglobin was < 10g/dL (67,1%). The result of bivariate analysis using ChiSquare showed that there were not correlation between type of delivery and primary postpartum hemorrhage (p:0,583), between age and primary postpartum hemorrhage (p: 1,000), but in another variabel there were correlation between parity and primary postpartum hemorrhage (p:0,003), amount of hemoglobin and primary postpartum hemorrhage (p: 0,000). The result of multivariate using regression logistic showed the most significant risk factor was the amount of hemoglobin as the main cause of primary postpartum hemorrhage